VIII.6 On the Pointwise Asymptotic Behavior of Generalized Solutions 557
and we have used the fact that e
1
×x · ∇(∇E) −e
1
×(∇E) = 0. Taking into
account that supp (θ) ⊂ B
3R
, we find that the function G satisfies
k∇ · Gk
2
≤ c
1
(R) R (k∇ · Fk
2
+ []F[]
2,R
+ |Φ|) ,
[|G|]
2,R
≤ c
1
(R)R([]F[]
2,R
+ |Φ|) .
(VIII.6.7)
We also observe that using several times the embedding Theorem II.3.3 and
the properties of w given in (VI II.6.5), we deduce
kgk
6
≤ c
2
([]F[]
2,R
+ kvk
2,2,Ω
2R
+ kqk
1,2,Ω
2R
+ kv
∗
k
3/2,2,∂Ω
) , (VIII.6.8)
with c
2
= c
2
(R, B), whenever R, T ∈ [0, B]. Thus, in view of (VIII.6.7),
(VIII.6.8), we check that the hypotheses of Theorem VIII.5.1 are satisfied, and
consequently, there exists a t least one solution (u, q) to (VIII.6.6) satisfying all
the properties listed in tha t theorem. Again by Theorem VIII.5.1, this solution
is unique in the class of generalized solutions, and so we must have u = u
and q = q + q
0
, where q
0
∈ R. However, q ∈ L
6
(R
3
) and q ∈ L
r
(R
3
), for all
r > 3/2, which impl ies q
0
= 0. Thus, recalling that u = v and q = p in Ω
2R
,
from Lemma VIII.6.1, (VIII.6.7), (VIII.6.8), (VIII.5.3), and the inequality
kpk
q,Ω
2R
≤ c
1
(R, q)kpk
6,Ω
≤ c
2
(R, q)|p|
1,2
, q ∈ [1, 6] , (VIII.6.9)
we find, on the one hand, that v, p satisfy (VIII.6.3), and on the other hand,
that they satisfy the estimate
kD
2
vk
2,Ω
2R + k∇vk
2,Ω
2R + []v[]
1,R,Ω
2R + kpk
r,Ω
2R + k∇pk
2,Ω
2R
≤ C([]F[]
2,R
+ k∇· F k
2
+ kv
∗
k
3/2,2,∂Ω
+ kvk
2,2,Ω
2R
+ kpk
1,2,Ω
2R
) .
This latter, in turn, combined with Lemma VIII.6.1 and with (VIII.6.9), yields
|v|
2,2
+ |v|
1,2
+ []v[]
1,R
+ |p|
1,2
+ kpk
q
1
+ kpk
q
2
,Ω
2R
≤ C ([]F[]
2,R
+ k∇ · F k
2
+ kv
∗
k
3/2,2,∂Ω
+ kvk
2,Ω
3R
+ kpk
2,Ω
3R
) ,
(VIII.6.10)
where C = C(Ω, R, q
1
, q
2
, B). By means of a standard argument that we have
already used several times, we will now show that
kvk
2,Ω
3R
+ kpk
2,Ω
3R
≤ C(k∇·Fk
2
+ []F[]
2,R
+ kv
∗
k
3/2,2,∂Ω
) , (VIII.6.11)
for some constant C satisfying the property stated in the theorem. Then,
combining (VIII.6.11) with (VIII.6.10 ), we will obtain (VIII.6.4), and this
will conclude the proof of the theorem. Assume that (VIII.6.11) does not
hold. Then, in view of the linearity of problem (VIII.0.2), (VIII.0.7), we can
find a sequence {F
n
, v
∗n
, R
n
, T
n
}, with R
n
, T
n
∈ [0, B], and a sequence of
corresponding solutions {v
n
, p
n
} such that
[|F
n
|]
2,R
n
+ k∇· F
n
k
2
+ kv
∗n
k
2−1/q,q,∂Ω
≤
1
n
,
kv
n
k
q,Ω
3R
+ kp
n
k
q,Ω
3R
= 1.
(VIII.6.12)